2023
DOI: 10.3390/membranes13120896
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the Novel Slot Blot Method with a PVDF Membrane for Protein Identification and Quantification in Kampo Medicines

Takanobu Takata,
Togen Masauji,
Yoshiharu Motoo

Abstract: Kampo is a Japanese traditional medicine modified from traditional Chinese medicine. Kampo medicines contain various traditional crude drugs with unknown compositions due to the presence of low-molecular-weight compounds and proteins. However, the proteins are generally rare and extracted with high-polarity solvents such as water, making their identification and quantification difficult. To develop methods for identifying and quantifying the proteins in Kampo medicines, in the current study we employ previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 120 publications
(314 reference statements)
0
1
0
Order By: Relevance
“…Tominaga et al reported that the aqueous methanol extract of Drosera tokainsis inhibits the generation of CML and CMA from ribose-derived gelatin in vitro [ 114 ]. Although Kampo medicines should generally be administered orally and their compounds are metabolized to exert effects in the human body, previous research provides important background [ 43 , 44 , 45 , 115 ]. Studies in which the characteristics of Kampo medicines are reproduced must clarify their effects against intra- and extracellular AGEs in vitro and in vivo [ 1 ].…”
Section: Effects Of Kampo Medicines On Intra- and Extracellular Agesmentioning
confidence: 99%
“…Tominaga et al reported that the aqueous methanol extract of Drosera tokainsis inhibits the generation of CML and CMA from ribose-derived gelatin in vitro [ 114 ]. Although Kampo medicines should generally be administered orally and their compounds are metabolized to exert effects in the human body, previous research provides important background [ 43 , 44 , 45 , 115 ]. Studies in which the characteristics of Kampo medicines are reproduced must clarify their effects against intra- and extracellular AGEs in vitro and in vivo [ 1 ].…”
Section: Effects Of Kampo Medicines On Intra- and Extracellular Agesmentioning
confidence: 99%